2013
DOI: 10.1103/physrevb.88.024505
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of charge modulations in La1.875Ba0.125CuO4and YBa

Abstract: A charge modulation has recently been reported in (Y,Nd)Ba2Cu3O6+x [Ghiringhelli et al. Science 337, 821 (2013)]. Here we report Cu L3 edge soft x-ray scattering studies comparing the lattice modulation associated with the charge modulation in YBa2Cu3O6.6 with that associated with the well known charge and spin stripe order in La1.875Ba0.125CuO4. We find that the correlation length in the CuO2 plane is isotropic in both cases, and is 259 ± 9Å for La1.875Ba0.125CuO4 and 55 ± 15Å for YBa2Cu3O6.6. Assuming weak … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 32 publications
5
49
0
Order By: Relevance
“…does not significantly depend on the material family. A similar conclusion was reached by resonant soft x-ray diffraction 49 . In contrast, the accompanying magnetic fluctuations are strongly familydependent, suggesting that charge order is an intrinsic feature of the CuO 2 planes around 1/8 doping, with the strength of associated spin fluctuations determined by the underlying AFM tendencies of the family.…”
Section: Discussionsupporting
confidence: 79%
“…does not significantly depend on the material family. A similar conclusion was reached by resonant soft x-ray diffraction 49 . In contrast, the accompanying magnetic fluctuations are strongly familydependent, suggesting that charge order is an intrinsic feature of the CuO 2 planes around 1/8 doping, with the strength of associated spin fluctuations determined by the underlying AFM tendencies of the family.…”
Section: Discussionsupporting
confidence: 79%
“…peak below T c [ Fig. 3(b)] shows that soft CCMs are suppressed by superconductivity and compete with it, in analogy to what has been observed in YBCO, where the soft CCM peak weakens and broadens below T c , but is restored by an external magnetic field [8,10,11,13]. We note that at T c the soft CCM peak is broader in Bi2212 than in YBCO, and that the incommensurate wave vector is slightly different.…”
Section: K From Experiments No2 [Black Triangles Insupporting
confidence: 71%
“…On the other hand, a short range checkerboard or stripe-like order over a wide doping range has been re- [4,[6][7][8] ported by STM [19][20][21][22][23]. The characteristic wave vector is q ≃ 0.25 r.l.u.…”
Section: K From Experiments No2 [Black Triangles Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the assumption that all of the measurements are probing the same CDW correlations, it has been proposed that the X-ray measurements might be integrating over fluctuating CDW correlations, which would not be detectable by NMR 48,49 . There are problems with such an interpretation, however, a recent study 50 has shown that the integrated intensity of a CDW peak in YBa 2 Cu 3 O 6.6 is quite similar to one in charge-stripe-ordered La 1 NiO 4 , our results directly demonstrate that charge-stripe fluctuations exist far above T co , whereas elastic X-ray scattering measurements 16 lost the signal by T co þ 20 K. This strongly suggests that the X-ray studies of YBa 2 Cu 3 O 6 þ x are measuring static correlations. (Note that recent inelastic X-ray scattering measurements 51 have narrowed the possible energy range of fluctuations to something less than 1 meV.)…”
Section: Discussionmentioning
confidence: 97%